Agent-whistleblower Technology for Secure Internet of Things - Eliseev, Vladimir; Gurina, Anastasiya (Journal of Science and Technology on Information security, 2020)
Abstract— The paper investigates the causes of widespread use by cybercriminals of the Internet of Things for organizing network attacks and other illegal use. An analysis of existing approaches and technologies for protecting networked computer devices is presented, as well as the main factors that prevent their use in the world of Internet of Things. An approach is suggested that ensures the integration of protective mechanisms directly into the composition of Things. Various variants of technology implementation are considered. Key aspects and potential ways of implementing the proposed approach are noted. Tóm tắt— Bài báo nghiên cứu về các phương thức được tội phạm mạng sử dụng rộng rãi trong Internet vạn vật (IoT), để tổ chức các tấn công mạng và các hành vi bất hợp pháp khác. Bài báo phân tích các phương pháp và công nghệ hiện có để bảo vệ các thiết bị kết nối mạng, cũng như các yếu tố chính để ngăn chặn việc sử dụng chúng trong IoT. Cách tiếp cận được đề xuất là đảm bảo việc tích hợp các cơ chế bảo vệ trực tiếp vào cấu trúc của IoT. Bài báo cũng xem xét các biến thể khác của việc thực hiện công nghệ này. Từ đó, đưa ra lưu ý về các khía cạnh chính và cách thức cài đặt tiềm năng để thực hiện phương pháp được đề xuất.